QUA VADIS UPBRINGING? - Medne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The necessity to address the topicality of problems of upbringing in a family was determined by active discussions in the public space in Latvia regarding the following issues: problematic (aggressive) behaviour of children (Delfi, 2013), the legitimisation of artificially invented diagnoses (Raipulis, 2008; Medne, 2012), and the imitation of pedagogical activities (upbringing) (Medne, 2012). This discussion is becoming more topical regardless the fact that various types of training are regularly organised for parents. The objective of this article discloses an attempt to analyse the social situations of development theoretically as the upbringing context by interpreting the social situation of development as active, equal in rights, humane, systematic, common day-to-day activities both at declarative and implementation levels.